2014
DOI: 10.1136/bmjqs-2013-002361
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transforming healthcare delivery on cystic fibrosis outcomes: a decade of quality improvement at Cincinnati Children’s Hospital

Abstract: BackgroundIn 2001, Cincinnati Children's Hospital embarked on a journey to improve healthcare delivery to patients with cystic fibrosis (CF). Data from the Cystic Fibrosis Foundation National Patient Registry revealed our below-average clinical outcomes, prompting us to initiate improvement interventions.ObjectiveTo improve clinical outcomes for patients with CF through a comprehensive quality-improvement approach directed at increasing patient centredness and improving healthcare delivery.InterventionsIn 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…A single‐center study that defined rapid decline as a decrease in FEV 1 of more than 10% predicted within the prior 12 months from the maximum observed FEV 1 showed that subsequently treating patients according to this decision rule corresponded to mean improvements in overall FEV 1. A similar study at another CF center corroborated these findings . Early detection of rapid decline or its impending onset would enable early treatment, and potentially prevention.…”
Section: Introductionmentioning
confidence: 99%
“…A single‐center study that defined rapid decline as a decrease in FEV 1 of more than 10% predicted within the prior 12 months from the maximum observed FEV 1 showed that subsequently treating patients according to this decision rule corresponded to mean improvements in overall FEV 1. A similar study at another CF center corroborated these findings . Early detection of rapid decline or its impending onset would enable early treatment, and potentially prevention.…”
Section: Introductionmentioning
confidence: 99%
“…1 Quality improvement programs (QIPs) to advance the medical care of patients with CF are effective in improving outcomes and survival. 2 QIPs with published results include improving the treatment of inpatient pulmonary exacerbations, 3,4 airway clearance techniques, 4 quarterly visits, 5 and nutritional outcomes. 5,6 These programs were supported by the CF Foundation through the Leadership and Learning Quality Improvement Collaborative.…”
mentioning
confidence: 99%
“…23 Although this is vital for the healthcare facility aspect of the cocreation process, identifying positive deviant patients may be a critical next step. Whilst the Cincinnati Children's hospital cystic fibrosis case study demonstrated a patient recruitment and partnership process for co-design, 37 the application of PD may have generated a higher value impact on co-creation through the synergy of positive deviant facilities with positive deviant patients and family members. The same process that was used to identify positive deviant facilities may be used to identify positive deviant patients.…”
Section: The Development Of a Positive Deviant Co-creation Groupmentioning
confidence: 97%